THE IMPORTANCE OF ART IN DEPICTING THE IMAGE OF A DOG (ON THE EXAMPLE OF NAVOI'S LYRICS) - Xasanova, Laylo (Журнал иностранных языков и лингвистики, 2021)
This article is a scientific observation about the image of a dog in Alisher Navoi lyrics and its textual meaning. The mystical meanings of the image of the dog in the poet's work are explained on the basis of examples. So, this text is described the importance of art in depicting the image of a dog.